Avetik Isahakyan’s Love Poetry in Translations by Mikhail Dudin - Z. G. Ayryan (Научный диалог, 2017)
The article is devoted to translations of the love poetry of Avetik Isahakyan by M. Dudin. It is noted that Isahakian’s poetry is the pinnacle of Armenian literature, and it is no coincidence that the poet even during his lifetime was named the Master. The themes of motherland, civil worldview, love and nature can be considered major in his poetry. The author believes that the poet’s philosophical reflections reveal his deep inner world. With the end of the first half of the 20th century the poetry by Avetik Isahakyan was translated by the poets like A. Akhmatova, E. Nikolaevskaya, V. Zvyagintsev, I. Snegova, M. Dudin and others. By comparative analysis the article investigates translations of Isahakyan’s love lyrics by M. Dudin. This work allows to evaluate the quality of poems translated from Armenian into Russian and their compliance with the originals. The study showed that the translations correspond to the original poetic texts in meaning and style, so they felt the spirit of the national culture and the mood of the Armenian poet. It is shown that the translations of M. Dudin proved him a wizard of rhyme, who cleverly weaved in it the figurative and expressive means showing the wealth and sophistication of the poetic language of the Russian poet.